2018
DOI: 10.1159/000486306
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Variability in Acute Ischemic Stroke: Influence of Infarct Location in the Insular Cortex

Abstract: Background: The aim of this study was to elucidate the influence of insular infarction on blood pressure (BP) variability and outcomes according to the region of the insular cortex affected. Methods: A total of 90 patients diagnosed with acute unilateral ischemic stroke were registered. The BP variability was calculated over 24 h after admission (hyperacute) and for 2–3 days after admission (acute). Patients were classified into groups of right and left, and then right anterior, right posterior, left anterior,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Vascular compression on the rostral ventrolateral medulla and insular infarction are often discussed as components of the central nervous system that influence autonomic dysfunction. As shown in our previous study, these factors are associated with BP variability in patients with AIS . In addition, increased short‐term BP variability is associated with autonomic nervous dysfunction, such as an enhanced sympathetic drive and an impaired baroreflex function .…”
Section: Discussionsupporting
confidence: 61%
“…Vascular compression on the rostral ventrolateral medulla and insular infarction are often discussed as components of the central nervous system that influence autonomic dysfunction. As shown in our previous study, these factors are associated with BP variability in patients with AIS . In addition, increased short‐term BP variability is associated with autonomic nervous dysfunction, such as an enhanced sympathetic drive and an impaired baroreflex function .…”
Section: Discussionsupporting
confidence: 61%
“…The association between BP variability during the acute stage of ischemic stroke and outcomes has been investigated recently, but the relationship remains unclear. Various factors, such as brain edema, hemorrhagic www.nature.com/scientificreports www.nature.com/scientificreports/ transformation, vessel recanalization, increased sympathetic drive, and mental stress at admission, affect acute-phase BP levels [17][18][19][20] . In addition, reactive hypertension occurs after the onset of stroke, and elevated BP levels fall remarkably during the first 7 days of onset, with little change thereafter 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Brain territories responsible for BP variability have been investigated in several studies, and recently Kitamura et al . showed that BP variability in the hyperacute phase tended to be low in patients with right insular infarction and high in those with left insular infarction 28 . However, this effect persisted only in the hyperacute phase for the first 24 hours after admission.…”
Section: Discussionmentioning
confidence: 96%